Analisis Kinerja Keuangan Dan Ukuran Perusahaan Terhadap Harga Saham Studi Empiris Pada Perusahaan Sektor Finansial Yang Terdaftar Di Bursa Efek Indonesia Periode 2017-2019 - Asri Maria Magdalena Tamba; Meinarni Asnawi; Novalia Herlina Bleskadit (Fakultas Ekonomi dan Bisnis, Universitas Cenderawasih, 2021)
Stock prices show a reference for investors in making investment decisions, stock prices often change according to supply and demand teams. period 2017-2019. Sample selection was done by using purposive sampling technique. In this study, the sample used was the Financial Sector companies listed on the Indonesia Stock Exchange for the 2017-2019 period as many as 52 companies with the amount of data processed for 3 years, namely 156 companies. The type of data used is secondary data obtained from the Indonesia Stock Exchange website, namely www.co.id in the form of company financial statements. In this study using multiple analysis tools using the SPSS program with version 21.0. The regression equation of this study is Y = -1.523 + 0.863 X1 + 0.603 X2. The results of this study indicate that ROA has no effect on stock prices. while Roe has a positive and significant influence on stock prices. Meanwhile, Roi has no effect on stock prices and Size has no effect on stock prices.